LEÑOS GIMNOSPÉRMICOS DE LA FORMACIÓN MELO (PÉRMICO INFERIOR) URUGUAY. PARTE IIl. PAULISTOXYLON,AUSTROSCLEROMEDULLOXYLON y PIRACICABOXYLON (Ameghiniana, 2014)
Three species of Cordaitales from Arroyo Seco (Rivera Department, Uruguay) of Early Permian age (Melo Forrnation) are described. Austroscleromedulloxylon geraldinii Mussa and Paulistoxylon inflatum Mussa have tabicated piths while Piracicaboxylon meloi n. sp. is characterized by pith differentiated in two zones (central and outer areas) separated by a parenchymatic ring. They all possess primary xylem with wedgeshaped projections and pycnoxylic secondary xylem, with well marked growth rings.